Non-Secretor "A" Subgroup with Acquired B Antigen, Naturally & Acquired Immune Anti-A1 Antibodies in a Patient with Carcinoma of Esophagus - Nadeem Nusrat, Bippin Nepal, Saddam Hussain, Zaen Pahore, Akbar Agha, Saima Minhas, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
ABO blood group system is one of the most important in clinical transfusion medicine. Numerous ABO discrepancies are seen during routine blood banking and they should be properly sorted out for a safe blood transfusion. During usual blood grouping we found a patient with carcinoma of esophagus having “A” Sub Group, acquired B antigen along with a non-secretor status. The patient was referred to the blood bank of DDRRL, Dow University of health sciences, Karachi, Pakistan, for transfusion due to severe anemia. The aim of this case report is to have a heightened awareness of blood sub-groups especially in patients with malignant diseases and performance of reverse grouping as a routine which is carried out in quality care transfusion services The first choice of blood group for transfusion is the A subgroup followed by O blood group. As the patient had already received A1 blood group, so in addition to the naturally occurring cold antibodies, he had developed warm anti A antibodies so A blood transfusion should be avoided in him.